Impact of Covid-19 on Stock Market in Sub-Saharan Africa - Saifullahi Adam Bayero; Babangida Danladi Safiyanu; Zaitun Sanusi Bakabe (Research Synergy Foundation, 2021)
Corona virus disease (COVID-19) which was declared by the World Health Organization as a global pandemic caused serious economic problem to all the countries including Sub-Saharan Africa. Given the negative impact of COVID19 on the world economy, this paper examined the impact of COVID19 related cases and death on stock exchange markets volatility in Sub-Saharan African countries. The study used the number of reported cases and death from four Sub-Saharan African countries viz Nigeria, South Africa, Kenya, and Botswana, reported cases and death from China and U.S. and all share index as a proxy of stock markets in four countries from 28 February 2020 to 21 December 2020. The study estimated GARCH 11, TGARCH 11, and EGARCH 11 since the variables are heteroskadestic in nature which makes the application of ARCH lausible; the selection criterion was based on Akaike, Schwarz, and Hannan info Criteria. The result shows that COVID19 confirmed cases and death do not affect the operation of the stock markets in Sub-Saharan African countries, but the volatility of the markets has increased within the period of analysis. Furthermore, Botswana and Kenya stock markets were affected by external cases from China. We therefore recommended that stock markets stakeholders in Sub-Saharan Africa should be more concern about health safety measures and be ready for any future pandemic that might affect the markets.